(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Digital document is now widely used and actively growing. Any digital document should be relevant, authentic and reliable before being presented in court as evidence. Thus, the basis of this study to determine the admissibility of a digital document from Islamic perspectives particularly the theory, opinion from scholars, law provisions, and the classification of the digital document from Islamic perspectives. This study used content analysis methods on a variety of data obtained including classical and modern legal books, scholarly opinions including books, journal articles, reports, standards, internet publications, and government documents. This study suggests whether the Islamic perspectives only highlight the official and unofficial documents and the is it required for having current classification in this new era? It because to ensure that we do not justify the wrong jurisdiction related to the digital document of topic Artificial Intelligence (AI), Virtual Reality (VR), and Augmented Reality (AR) for extensive view related to digital document from Islamic perspectives.